Safety management practices for hazardous materials - Cheremisinoff, Nicholas P. (Marcel Dekker, 1996)
This unique resource explains the interrelationships between safety regulations and environmental regulations and stresses skills and techniques in the management of environmental policy and corporate safety policy, particularly for complex industrial facilities - discussing Occupational Safety and Health Administration (0SHA) and Department of Transportation (DOT) regulations; as well as the Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA); the Resource Conservation and Recovery Act (RCRA); the Clean Air Act; the Clean Water Act; and many others.